(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
This work has as its primary objectives the popularization of Aristophanes’ Greek comedy through an adaptation of the play Lysistrata (411 BC) for the Animated Theater by Grupo Paideia, in order to make the work accessible to another public, not only the erudite. It also aims to relate the masks and puppets elements, in the context of staging, taking into account the laughable and the grotesque in both elements.